2004
DOI: 10.1079/ahr200483
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of the pathogenesis ofMannheimia haemolyticaandHaemophilus somnusinfections: challenges and potential opportunities for prevention?

Abstract: Progress in producing improved vaccines against bacterial diseases of cattle is limited by an incomplete understanding of the pathogenesis of these agents. Our group has been involved in investigations of two members of the family Pasteurellaceae, Mannheimia haemolytica and Haemophilus somnus, which illustrate some of the complexities that must be confronted. Susceptibility to M. haemolytica is greatly increased during active viral respiratory infection, resulting in rapid onset of a severe and even lethal ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 51 publications
0
28
0
2
Order By: Relevance
“…This is similar to the shipping fever model of respiratory disease in domestic livestock. The shipping fever model views pasteurellosis as an opportunistic disease that results when endogenous Pasteurellaceae colonize the lungs of livestock compromised by different combinations of infectious agents, host and environmental determinants [23, 24, 208–210]. This model arose subsequent to the failure of single-agent experiments to provide an explanation for shipping fever.…”
Section: Determinants Limiting Free-ranging Bighorn Sheep Populationsmentioning
confidence: 99%
“…This is similar to the shipping fever model of respiratory disease in domestic livestock. The shipping fever model views pasteurellosis as an opportunistic disease that results when endogenous Pasteurellaceae colonize the lungs of livestock compromised by different combinations of infectious agents, host and environmental determinants [23, 24, 208–210]. This model arose subsequent to the failure of single-agent experiments to provide an explanation for shipping fever.…”
Section: Determinants Limiting Free-ranging Bighorn Sheep Populationsmentioning
confidence: 99%
“…Studies have shown that several characteristics or activities of this bacterium contribute to its virulence. An exotoxin, leukotoxin, is considered the most important virulence factor associated with M. haemolytica (6). Leukotoxin is responsible for M. haemolytica hemolysis on blood agar and causes leukocyte necrosis and apoptosis in vivo , thus allowing the bacterium to escape phagocytosis and killing by neutrophils and macrophages (7, 8).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Bacterial species include Pasteurella multocida , Mannheimia haemolytica , Histophilus somni , and Mycoplasma bovis . Studies suggest that it is the interaction of these pathogens and the failure of the animal’s immune system that produce full-blown disease (13). These same sources point to the possibility that bacterial pathogens cause the acute syndrome by invading the bovine respiratory tract that has been compromised by viral infections, environmental conditions, and/or other stress factors such as comingling, dehydration, and crowding during shipping (4, 5).…”
Section: Genome Announcementmentioning
confidence: 99%